МІКРОБІОЛОГІЧНА АКТИВНІСТЬ ТА ЕКОЛОГІЧНИЙ СТАН СІРОГО ЛІСОВОГО ҐРУНТУ ПРИ ЗАСТОСУВАННІ ДЛЯ ЗРОШЕННЯ МІСЬКИХ СТІЧНИХ ВОД - Дишлюк, В. Є. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2018)
The results of studies of the effect of irrigation with biologically purified urban wastewater on thebiological activity of grey forest soil and its environmental state are presented. Irrigated by wastewaterunder optimal mineral agrarian background provided comfortable conditions for the activity ofmicrobiota and increased biological activity of soil. According to the parameters of total biologicalactivity, irrigated soil is classified as anthropogenically degraded with a good environmental condition.